Microbiota and Ageing - Fernández Contreras, María Encarnación (My University, 2024)
The World Health Organization (WHO) has defned healthy ageing as the process of developing and maintaining the functional ability that enables well-being in older age. Functional ability means having the capabilities to enable people to be and do what they value. It is referred to as the ability [1]: ¿ To meet their basic needs. ¿ To learn, grow and make decisions. ¿ To be mobile. ¿ To build and maintain relationships. ¿ To contribute to society. At the biological level, ageing results from the impact of the accumulation of a wide variety of molecular and cellular damage over time. This leads to a gradual decrease in physical and mental capacity, a growing risk of disease and, eventually, death. Older age is also characterized by the emergence of several complex health states commonly called geriatric syndromes. They are often the consequence of multiple underlying factors and include frailty, urinary incontinence, falls, delirium and pressure ulcers. Health conditions commonly associated with age include neurodegenerative, cardiovascular or musculoskeletal disorders, as well as diabetes, most of them sharing an infammatory/immunological component. This led to the creation of a new term: ¿infamm-ageing¿ or ¿infammageing¿, defned as an age-related increase in the levels of blood and tissue pro-infammatory markers [2]. As people age, they are more likely to experience several conditions at the same time. Gut microbiota has gained increasing relevance among the multiple factors related with age. Recent research points out to an impact on human health and ageing processes. Dysbiosis is a risk factor for age-related diseases, but, in contrast, the presence of a wide variety of microbial taxa has been claimed to increase life expectancy. Indeed, signifcant differences in the composition of gut microbiota between centenarians and younger elderly have been reported [3, 4]. Hence, microbiota might play a key role in the so-called healthy ageing, and, more interestingly, it is emerging as a promising target for anti-ageing therapies.